Developmental Genes and Malformations in the Hypothalamus - Diaz, Carmen; Puelles, Luis (Frontiers in Neuroanatomy, 2020)
The hypothalamus is a heterogeneous rostral forebrain region that regulates physiological processes essential for survival, energy metabolism, and reproduction, mainly mediated by the pituitary gland. In the updated prosomeric model, the hypothalamus represents the rostralmost forebrain, composed of two segmental regions (terminal and peduncular hypothalamus), which extend respectively into the non-evaginated preoptic telencephalon and the evaginated pallio-subpallial telencephalon. Complex genetic cascades of transcription factors and signaling molecules rule their development. Alterations of some of these molecular mechanisms acting during forebrain development are associated with more or less severe hypothalamic and pituitary dysfunctions, which may be associated with brain malformations such as holoprosencephaly or septo-optic dysplasia. Studies on transgenic mice with mutated genes encoding critical transcription factors implicated in hypothalamic-pituitary development are contributing to understanding the high clinical complexity of these pathologies. In this review article, we will analyze first the complex molecular genoarchitecture of the hypothalamus resulting from the activity of previous morphogenetic signaling centers and secondly some malformations related to alterations in genes implicated in the development of the hypothalamus.